ELEMENTAL COMPOSITION OF DIFFERENT PARTS OF MORINGA OLEIFERA BY X RAY FLUORESCENCE TECHNIQUE FROM SEMI-ARID CLIMATIC REGION - R. Ram, Rajesh; Ram, Vijay R.; Vyas, Suhas J.; Dave, Pragnesh N. (IJRDO -JOURNAL OF MATHEMATICS, 2016)
The objective of the present investigation was to study the elemental composition of bark,flower, leaves, seed and seed cover of Moringa oleifera is a species of tree native to Indiagrowing in semi-arid region of Kachchh district, Gujarat, India. The Bark, flower, leaves, seedand seed cover of Moringa oleifera were subjected to Energy Dispersive X-ray Fluorescence(EDXRF) and were analyzed for different mineral composition. As the X-ray Fluorescence isone of the most reliable and accurate, as well as it is also a consistent and non-destructivemethod for analysis of major and trace elements using a single pressed pellet. During the study itwas found that maximum amount of oxides in bark sample was calcium oxide which was 52.6%, in flowers sample it was potassium oxide which was 34.2%, in leaves sample was calciumoxide which was 42.9 %, in seed sample was potassium oxide which is 95.0 % and in seed coversample was potassium oxide which is 67.9 %.